LOS CAMPESINOS QUIEREN DECIR... - Arguedas Marín, Cecilia (1994)
This paper presents and analyses the alternative proposal, elaborated by the justice and Development Peasant Counsel -costarrican peasant social movement-. It's a proposal against economical policies, directed to the sector and impeled by structural adjustment policies.